Les schèmes de régulation de l'activité des enseignants - Roland Goigoux (Nantes Université, 2018)
In this article, the author comments and expands on two of the contributions contained in the dossier entitled "The Categorization of Persons in Teaching and Learning". These two contributions deal with the cognitive functioning of teachers when they are interacting with their students. The author suggests several ways to overcome the pitfalls he identifies and introduces some complementary theoretical elements. He concludes by illustrating his recommendations with an example of empirical research on how teachers regulate their action according to that of their students.